Reaching the MDGs : An Action Plan for Trade - McDonald, Brad.; Elborgh-Woytek, Katrin; Gregory, Rob. (Washington, D.C. : International Monetary Fund, 2010)
The actions proposed here focus on trade integration, substantially increasing exports of the poorest countries and helping them to meet the Millennium Development Goals. As the foundation for these ambitions, we emphasize the role of a secure, open global trading environment-strengthened further by concluding the WTO Doha Round. From this base, the poorest countries also need better trade preferences from the advanced and major emerging market countries (EMs). Building the capacity to take advantage of trade opportunities will require support from the international community and policy reforms-such as to trade regimes-by the poorest countries themselves. The Fifteen Point Action Plan proposed here could increase annual exports of the least-developed countries (LDCs) by USD 10 billion or more, with additional benefits for other Low-Income Countries (LICs).
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet